Recurrent cardiac tamponade: an initial presentation of lung adenocarcinoma. (21st May 2014) - Kumar, Aditi; Puttanna, Amar
Abstract : A 63-year-old hypertensive woman presented initially to the surgical team with right upper quadrant pain, the patient was otherwise asymptomatic and clinically well. An abdominal CT scan excluded any surgical diagnoses but rather showed a pericardial effusion. When the cardiology team urgently reviewed her, they found her to be hypotensive and tachycardic with a raised jugular venous pressure. A diagnosis of cardiac tamponade was made and was transferred to the coronary care unit for an emergency pericardiocentesis. She developed tamponade on further occasions requiring pericardiocentesis. The underlying cause was investigated and following pericardial fluid analysis and subsequent imaging, metastatic lung adenocarcinoma was diagnosed.